Implicit motive profile analysis: An if-then contingency approach to the picture-story exercise - Schultheiss, Oliver; Schultheiss, Maria (Social and personality psychology compass, 2014)
Picture-story exercise (PSE) measures of implicit motives provide objective, stable, and valid scores. However, PSE scores are also characterized by substantial variability from one picture to the next, resulting in low internal consistency estimates. We argue that this variability is a critical source of the PSE's validity because it reveals stable if-then contingencies between the situational contexts represented by the picture cues and individuals' motivational responses to them. We also present the correspondence hypothesis, according to which the situational cues in the PSE are representative of specific real-life situations and a person's imaginative-story responses to the PSE cues therefore also reflect his or her real-life responses to such situations. We review corroborating research and discuss the implications of the if-then contingency approach for assessment, prediction, and for the measurement of motivational congruence. © 2014 John Wiley & Sons Ltd.